المقابر في العراق القديم - حسين، منتهى نعمة عودة (جامعة بغداد - كلية التربية ابن رشد, 2015)
يتناول البحث أهمية رمزية الموت في حضارة العراق القديم باعتبار الموت عنصرا من عناصر الوجود والعدم وفي ظل تلك العقيدة كان الاهتمام بالميت وحفظ جسد المتوفى من العوامل الداخلية والخارجية للجثة طقسا جنائزيا مهما فكان مهمتهم ضمن هذه الطقوس هو نقل الميت إلى العالم السفلي أو أرض اللا رجعة ومنطلقا من هذه العقيدة فكان لابد من تجهيز مراسم وطقوس الدفن ووضع الجثمان في القبر ووضع مواد وأدوات تخص المتوفى وحسب موضعه في تلك الفترة التي عاشها وتكتمل هذه المرحلة بالمراسم والطقوس الجنائزية التي تمثل سبب الموت واثر وقعه على الإحياء ومن هذا المشهد يصور الجوانب الأساسية لعقائد ما بعد الموت لسكان العراق القديم.
This paper deals with the importance of symbolic death of the ancient civilization of Iraq Under those creed attention was deceased and keeping the body of the deceased from the internal and external factors of the body was their mission in Dead transfer to the underworld or the land of irreversibility and the starting point of this doctrine was to be a ceremony and burial rites processing and put the body in the grave and put materials and tools for the deceased, according to its position in that period he lived and completed this phase funeral ceremonies and rituals, which represents the cause of death and the effect was signed on neighborhoods, and this scene depicts the basic aspects of the faiths after death to the people of ancient Iraq
Keywords: العراق القديم -- الموت -- المقابر